Management of Remnant or Recurrent Lesions after Endoscopic Papillectomy - Ichiro Yasuda; Saito Kobayashi; Kosuke Takahashi; Sohachi Nanjo; Hiroshi Mihara; Shinya Kajiura; Takayuki Ando; Kazuto Tajiri; Haruka Fujinami (Clinical Endoscopy, 2020)
Endoscopic papillectomy (EP) for ampullary adenomas achieves cure rates ranging from 76% to 90%, and recurrence rates are as high as 33%. If remnant or recurrent lesions after prior EP are endoscopically visible and are not suspected of intraductal extension into the biliary or pancreatic duct, repeated snaring and cutting can be performed until all visible lesions are completely resected. However, endoscopic ablative therapies, particularly argon plasma coagulation, can be attempted for tiny or uncertain remnant and recurrent lesions. In addition, intraductal radiofrequency ablation has recently been attempted for residual intraductal lesions after EP at several institutions. Although still under investigation, it has shown some promise. It might be offered as an alternative to surgery, particularly in patients who are unfit for surgery or those who refuse to undergo surgery.